2021
DOI: 10.20944/preprints202111.0208.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patent Analysis Using Vector Space Model and Deep Learning Model : A Case of Artificial Intelligence Industry Technology

Abstract: Thanks to rapid development of artificial intelligence technology in recent years, the current artificial intelligence technology is contributing to many part of society. Education, environment, medical care, military, tourism, economy, politics, etc. are having a very large impact on society as a whole. For example, in the field of education, there is an artificial intelligence tutoring system that automatically assigns tutors based on student's level. In the field of economics, there are quantitative investm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The study found that AI patents have grown exponentially over time and cover a wide range of sub-fields. Yoo et al [4] proposed a method for analyzing AI patents using vector space models and deep learning models, like KeyBERT. A case study shows how the model can extract keywords and analyze relationships between AI technologies.…”
Section: Related Workmentioning
confidence: 99%
“…The study found that AI patents have grown exponentially over time and cover a wide range of sub-fields. Yoo et al [4] proposed a method for analyzing AI patents using vector space models and deep learning models, like KeyBERT. A case study shows how the model can extract keywords and analyze relationships between AI technologies.…”
Section: Related Workmentioning
confidence: 99%